Meta-neural-network for real-time and passive deep-learning-based object recognition - Jingkai Weng (Nature Portfolio, 2020)
The authors present a passive meta-neural-network for real-time recognition of objects by analysis of acoustic scattering. It consists of unit cells termed meta-neurons, mimicking an analogous neural network for classical waves, and is shown to recognise handwritten digits and misaligned orbital-angular-momentum vortices.